28 Initial experience of donegal cross border program between letterkenny university hospital (roi) and altnagelvin area hospital (ni). (5th October 2017) - Aleong, G; Peace, A; Sharif, Z; Tanner, R; Abdallah, S; David, S; McNeill, A; Crowley, J
Abstract : Introduction: County Donegal has traditionally been isolated as a result of its geographical remoteness from 24/7 Primary Percutaneous Intervention (PPCI) enabled centres in the Republic of Ireland. The National Acute Coronary Syndrome (ACS) programme is designed to increase access to PPCI for patients with ST Elevation Myocardial Infarction (STEMI). A cross-border initiative between the SAOLTA Hospitals, HSE, Republic of Ireland and the Western Health and Social Care Trust in Northern Ireland commenced on 5th May 2016 to provide PPCI for Donegal. We sought to evaluate the initial effectiveness of this unique Cross border PPCI pathway. Methods: ECG's from Donegal patients suspected of having a STEMI were transmitted from the National Ambulance Service (NAS) or Letterkenny University Hospital (LUH) ER to Altnagelvin Hospital PPCI service. All data were recorded for continuous audit purposes to assess performance indicators, ECG interpretation and the number of referrals made to the PPCI activator in Altnagelvin. All patients who had an ECG transmitted to Altnagelvin PPCI centre from May 2016 to March 2017 were included. Results: 139 patients were referred with a suspected STEMI to the Cross Border PPCI pathway with 88/139 patients (63%) referred from the National Ambulance Service (NAS); the rest referred from LUH ER. 95/139 (68%) patients were turned down. Only 44/139 patients were accepted for PPCI with a false activation rate of 32%. Only 30/139 patients actually had a final diagnosis of STEMI. The mean time from STEMI diagnosis on ECG to reestablishing flow in the culprit artery was 117.8 minutes within guidelines. No complications occurred during transfer and 89% were repatriated within 24 hrs. All 95 patients that were turned down were deemed appropriate with only 10/95 (10.5%) actually requiring PCI prior to discharge. Conclusion: Initial audit of this unique Cross Border PPCI pathway suggests that it is working effectively. The high referral rate and high rate of turn-downs suggest that diagnostic accuracy of ECG interpretation may need to be evaluated. The high rate of false activations is notable and also requires further investigation. The early success of this unique Cross border service is very encouraging when considering the geographical remoteness of Donegal. Work will continue to further improve this vital service for the people of Donegal.